2021
DOI: 10.1001/jamadermatol.2020.5598
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Individual-Aggregate Data on All-Cause Mortality in Bullous Pemphigoid

Abstract: The 1-year standardized mortality ratio (SMR) of bullous pemphigoid (BP) has been reported as 2.15 to 7.56 and lower in the US than in Europe.OBJECTIVE To estimate the worldwide 1-year SMR of BP.DATA SOURCES PubMed, Embase, Cochrane Library, Google Scholar, Lissa, and gray literature (eg, medRxiv) were screened for studies of BP published from inception to June 10, 2020, with review of reference lists. STUDY SELECTIONRetrospective and prospective studies reporting 1-year all-cause mortality rate in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 68 publications
1
20
0
3
Order By: Relevance
“…Patients were followed according to the schedule proposed in the EADV guidelines. Side‐effects of treatment were assessed, and their severity was graded according to the standard criteria of the World Health Organization 23,24 . Patients were followed for 1 year after BP diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were followed according to the schedule proposed in the EADV guidelines. Side‐effects of treatment were assessed, and their severity was graded according to the standard criteria of the World Health Organization 23,24 . Patients were followed for 1 year after BP diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Bullous pemphigoid is thought to be associated with neurologic disorders including dementia, multiple sclerosis, and Parkinson’s disease ( 85 ). Because it preferentially occurs in older adults with comorbidities and requires long-term use of systemic corticosteroids and immunosuppressive drugs, patients with bullous pemphigoid have a higher mortality rate (approximately 20%) than healthy older adults ( 86 ).…”
Section: Autoimmune Bullous Diseasesmentioning
confidence: 99%
“…Future studies also require appropriate control groups, longer follow‐up and a measure of person‐years in order to calculate mortality rates. A recent systematic review on all‐cause mortality in BP that included 56 studies reported that the overall quality of follow‐up was poor 8 . It is pertinent that researchers improve the reporting of mortality measures for these serious autoimmune blistering disorders.…”
Section: Figurementioning
confidence: 99%